MANAGEMENT OF HEALTH SERVICES IN SPORT - Nebojša Maksimović; Goran Vasić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Requirement for management of health service in sport has grown in recent years, along with sport development and organization of big sport events and manifestations. Good management of health service in sport is an excellent precondition of sportspeople's health, and a healthier sport nation, as well as better sports results. It has to be pointed out to all people dealing with sports that curing an injured or sick sportsman is not the only task of a sports doctor, which is expected too. The task is much more complex. It should include a series of prevention procedures, as well as permanent education of all people dealing with sports.